(untitled) (Research, Society and Development, 2022)
The benthic macroinvertebrate community is composed of some organisms that are more sensitive and others more resistant to environmental changes. In this sense, they are used as a bioindicator. The present work aimed to verify the local species diversity (alpha diversity) of the macroinvertebrate community in two stretches of the Lower Rio Grande Basin with distinct substrate composition. The study was carried out at two sites on the Rio Grande. At point 1, sediment samples were collected over a period of twelve months, where the diversity index of the parameters richness (S), abundance, dominance, Shannon-Wiener diversity (H’), Simpson diversity (D’) and equitability (J) were calculated and through the non-parametric Kruskal-Wallis analysis were compared between all the months of the year, as well as the rainy and dry seasons. At point 2, artificial objects were calculated and diversity indices were calculated, also including the rainy and estimation seasons. In point 1 there was no significant difference between the rainy and dry seasons, but there were differences in abundance and evenness between all months sampled. In point 2 it was evident that the diversity index values were higher during the dry season. In summary, it was inferred that the benthic communities may be under the reflex of environmental homogenization resulting from anthropic activities. Therefore, these diversity indices can be an adequate tool to understand the environment, and thus promote more assertive mitigation decisions in favor of the conservation of species.